A Review on the Degradation of Ionic and Non Ionic Surfactants in Water - Dutta, Dhiraj; Gaur, Nisha; Barman, Prabir; Ghosh, Debottam; Dubey, Rama; Dwivedi, Sanjai Kumar (Defence Life Science Journal, 2022)
The ability to respond to changing consumer and industrial wastes is critical for water treatment. Surfactants are of importance because of their increasing prevalence in home and industrial settings, as well as the challenges they provide to standard treatment. Surface active agents (SAAs) are chemical compounds that are discharged into the environment. They may have a deleterious impact on ecosystem biotic components. They also produce an increase in the aqueous phase solubility of organic contaminants. The destiny of SAAs in the environment is currently uncertain. Recognizing this issue will help to safeguard live species and maintain the quality and balance of a diverse ecosystem.This critical evaluation considers studies from several technical disciplines to offer an up-to-date summary of the environmental effects of surfactants. A variety of technologies are discussed, as well as their drawbacks and potential solutions.